A Comparison of the Plumage Condition of Three Egg-Laying Poultry Genotypes Housed in Non-Cage Systems - Zofia Sokołowicz; Magdalena Dykiel; Jadwiga Topczewska; Józefa Krawczyk; Anna Augustyńska-Prejsnar (Animals, 2023)
The study covered a total of 810 hens in 3 groups (housing systems) of 270 hens each. The plumage condition of laying hens raised in various types of alternative housing systems, i.e., in deep litter (B), free-range (FR), and organic systems (O), was assessed at 20, 36, and 56 weeks of age. The indoor stocking density was 6 hens/m2. The study included hens of the native Green-legged Partridge breed (Z-11), Rhode Island Red (R-11) hens covered by a genetic resource protection program, and hybrids of Hy-Line Brown. The plumage of the head, neck, back, tail, and abdomen was assessed on a 5-point scale. The assessment of individual hens' plumage was calculated as the sum of the scores of the head, neck, back, tail and abdomen and could range from 0 (no cover) to 20 points (full plumage). The type of alternative housing system implemented and the age of the laying hens had an effect on the plumage status of all body parts assessed (p < 0.05), while the genotype had an effect on the condition of the neck, back, and tail plumage (p < 0.05). In both the FR and O systems, the plumage status was similar and superior to that in B (p < 0.05). As the age of the birds increased, the condition of the hens' plumage deteriorated. The better state of the plumage in FR and O than in B may indicate improved levels of welfare in housing systems with access to outside runs.